CCL18‐dependent translocation of AMAP1 is critical for epithelial to mesenchymal transition in breast cancer. Issue 4 (27th September 2017) - Li, Haiyan; Zhang, Dawei; Yu, Jiandong; Liu, Hailing; Chen, Zhiping; Zhong, Haifeng; Wan, Yunle
Abstract : AMAP1 was a GTPase‐activating protein that regulates cytoskeletal structures in focal adhesions, circular dorsal ruffles, and promote cell differentiation in tumor cells. But the activation and function of AMAP1 in breast cancer remain largely unexplored. Here we show that AMAP1 was phosphorylated and translocated to plasma membrane and formed a stable complex with Pyk2 in response to CCL18. Moreover, CCL18‐dependent AMAP1 translocation interfered the AMAP1‐IKK‐β interaction, resulting in nuclear factor‐kappaB (NF‐κB) activation. Depletion of AMAP1 expression by RNAi efficiently reversed the CCL18‐induced epithelial to mesenchymal transition (EMT) of breast cancer cells and as well as CCL18‐induced adhesion, migration and invasion. Strikingly, AMAP1 overexpression was found in breast cancers that had undergone metastasis and was strongly predictive of poor prognosis in breast cancers. Given that AMAP1 mediated CCL18‐induce activation of NF‐κB and promoted breast cancer metastasis, AMAP1 may represent a therapeutic target for the eradication of breast cancer metastasis. Abstract : We show that AMAP1 was phosphorylated and translocated to plasma membrane and formed a stable complex with Pyk2 in response to CCL18. CCL18‐dependent AMAP1 translocation interfered the AMAP1‐IKK‐β interaction, resulting in nuclear factor‐kappaB (NF‐κB) activation, epithelial to mesenchymal transition (EMT), adhesion, migration, and invasion. AMAP1 overexpression was found in breast cancers that had undergone metastasis and was strongly predictive of poor prognoses in breast cancers.